2014
DOI: 10.1007/s00018-014-1733-x
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic control of TGF-β co-receptor activity by BMP-1/tolloid-like proteases revealed by quantitative iTRAQ proteomics

Abstract: The metalloproteinase BMP-1 (bone morphogenetic protein-1) plays a major role in the control of extracellular matrix (ECM) assembly and growth factor activation. Most of the growth factors activated by BMP-1 are members of the TGF-β superfamily known to regulate multiple biological processes including embryonic development, wound healing, inflammation and tumor progression. In this study, we used an iTRAQ (isobaric tags for relative and absolute quantification)-based quantitative proteomic approach to reveal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 65 publications
2
48
0
Order By: Relevance
“…In agreement with the specificity of the antibody used in Western blotting, the peptides observed by mass spectrometry cover the N‐terminal assembly domain of fibronectin. The precise cleavage site was then determined using a new approach called ATOMS (22, 23) coupled to TMT labeling and to a multienzymatic digestion. The 5 pep tides with the highest P:C ratios resulted from a unique and unambiguous cleavage site: V‐R‐AA 292 ↓ 293 Y‐Y‐Q,‐P (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with the specificity of the antibody used in Western blotting, the peptides observed by mass spectrometry cover the N‐terminal assembly domain of fibronectin. The precise cleavage site was then determined using a new approach called ATOMS (22, 23) coupled to TMT labeling and to a multienzymatic digestion. The 5 pep tides with the highest P:C ratios resulted from a unique and unambiguous cleavage site: V‐R‐AA 292 ↓ 293 Y‐Y‐Q,‐P (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Proteins were separated using SDS‐PAGE and stained with Coomassie blue. The cleavage site was determined by iTRAQ‐ATOMS according to the reported procedure (23). Investigation of testis morphology of WT or Adamts2 –/– males was performed by hematoxylin and eosin staining of paraffin‐embedded transversal sections.…”
Section: Methodsmentioning
confidence: 99%
“…These functions seem particularly coherent in the contexts of development, growth and tissue repair. However, recent proteomic studies aimed at discovering new BTP substrates [43] suggest that we are just beginning to uncover the full spectrum of their activities and that future studies will reveal new and unexpected roles. In this regard, the BTP regulatory proteins described above may represent interesting alternatives to target specific functions without affecting other activities of BTPs.…”
Section: Discussionmentioning
confidence: 97%
“…2; [42]), other proteinases such as MMPs and plasmin can perform the subsequent steps which consist in the degradation of LAP and in the release of active TGF-β1. More recently, we have shown that BTPs could also contribute to maintaining high levels of active TGF-β1 in tissues by promoting the degradation of two TGF-β antagonists (soluble betaglycan and CD109; [43]). …”
Section: Activation Of Signaling Moleculesmentioning
confidence: 99%
“…Evidence has previously been presented that BTPs may be involved in modulating TGFβ signalling via cleavage of the extracellular antagonist LTBP (Latent TGFβ Binding Protein) [17], and by cleavage of TGFβ co-receptors betaglycan and CD109 [55]. TGFβ can enhance ECM formation via recruitment of ECM-producing myofibroblasts and by up-regulation of many ECM-related genes, such as those encoding collagens I and III [22, 56].…”
Section: Discussionmentioning
confidence: 99%